MANFAAT EKONOMI DAN RISIKO TUNDA JUAL KOPI DI DESA TANJUNG REJO KECAMATAN PULAU PANGGUNG KABUPATEN TANGGAMUS - Yoandra Yoga Pratama; R Hanung Ismono; Fembriarti Erry Prasmatiwi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
Farmers will receive a low price when selling coffee at harvest period, so they are advised conducting trade delay. The research purposes were to analyze: economic advantage received by farmers conducting trade delay of coffee, price risk involved by farmers conducting trade delay of coffee, problems involved by farmers within trade delay of coffee, and influencing factors on farmer’s decision of conducting trade delay of coffee.  The research was conducted in Tanjung Rejo Village Pulau Panggung Subdistrict of Tanggamus Regency which chosen purposely. Total of samples were 61 farmers, consist of 31 trade delay of coffee farmers and 30 non trade delay of coffee farmers. The first purpose was analyzed by using the probability of loss and profit formula and the benefit within trade delay of coffee formula. The second purpose was analyzed by using coefficient variation.  The third and the last were analyzed by farmer’s perception and using logit method.  The results showed that economic advantage received by farmers conducting trade delay of coffee was increase of coffee price reached Rp2,073.79 per kg and profit Rp1,884,822.03 per year. CV was valued 0.04 which means trade delay system had low risk or potentially benefit farmers. Some problems faced by farmers were coffee bean storage (67.21%), indeterminacy of coffee price (55.74%), filling the household needs (49.18), pest attack (47.54%), and dried floor ownership (37.70%). Influencing factors on farmer’s decision of conducting trade delay of coffee were total of production, farmer’s household income, dried floor ownership, and coffee price in harvest period. Key words: economic advantage, risk, trade delay